(untitled) (Archaeologia Adriatica, 2025)
The paper presents the results of trial excavations at Vela Pećina cave near Kali on the island of Ugljan, and in particular the results of techno-typological and petrographic analyses of the lithic find assemblage. It considers the site’s significance in the settlement grid of Upper Palaeolithic hunter-gatherers within the context of the time period confirmed by radiocarbon dating and the site’s geographic location on the margins of the presently submerged Adriatic Plain.